Dysregulated MicroRNA Involvement in Multiple Sclerosis by Induction of T Helper 17 Cell Differentiation - Chen, Chen; Zhou, Yifan; Wang, Jingqi; Yan, Yaping; Peng, Lisheng; Qiu, Wei (Frontiers in Immunology, 2018)
Multiple sclerosis (MS) is an immune-mediated demyelinating disease of the central nervous system. Growing evidence has proven that T helper 17 (Th17) cells are one of the regulators of neuro-inflammation mechanisms in MS disease. Researchers have demonstrated that some microRNAs (miRNAs) are associated with disease activity and duration, even with different MS patterns. MiRNAs regulate CD4+ T cells to differentiate towards various T cell subtypes including Th17 cells. In this review, we discuss the possible mechanisms of miRNAs in MS pathophysiology by regulating CD4+ T cell differentiation into Th17 cells, and potential miRNAs targets for current disease-modifying treatments.